GERMINATION POWER AND GERMINATION OF HEMP SEEDS OF DIFFERENT SIZES - Конопля, К. В. (Scientific Progress & Innovations, 2013)
14 hemp varieties by the germination power and germination were investigated: 1) of the individual plants with the highest, middle and the lawest mass of 1000 seeds; 2) of the population of big, middle and small seeds group. In both investigations exceptionally normal ripe seeds without dependence with their group with dismission of factor of the negative influence of unripe seeds were analyzed. It was revealed that all groups of seeds of individual plants and populations give high indexes as by the germination power, as by germination. The fact of full value of small seeds as sowing material was proved.